Analisis Strategi Pemasaran Untuk Peningkatan Penjualan Pada Butik Tuhfah Style Kota Bekasi - Ramadani, Nita; Widiawati, Kristiana (JURNAL ADMINISTRASI KANTOR; Vol 11 No 2 (2023): Jurnal Administrasi Kantor (Desember 2023), 2023)
The fashion business is a business that has no end because along with the times, fashion models have begun to innovate a lot. The purpose of this study was to determine the marketing strategy through the approach Segmenting, Targeting, positioning and the marketing mix in increasing sales at Tuhfah Style boutiques. The method used in this research is descriptive qualitative by using three data collection techniques in the form of interviews, observation and documentation which was carried out with the owner. The results of this study indicate that the application of targets women aged 15 years and over and women who have income make the target at Tuhfah Style boutique classified as a target category for the upper middle class. The Marketing Mix at the Tuhfah Style boutique includes products that have premium quality and the latest models. Price (Price) offered in accordance with the ability of the community. An interesting and instagramable place. Promotion (Promotion) which is done by giving discounts and promotions on social media but has not been used to the fullest. People (Employees) apply the 3s system (smile, greet, greeting). Processes that are detailed and recorded can make payments easier for customers. Physical Evidence (Physical Evidence) sto relocated on the side of the road and accompanied by evidence of testimonials from customers on social media. Based on the constraints and  the results of the analysis above, a proposal was created to increase sales by using advertising on Instagram.   Keywords : Segmenting, Targeting, Positioning, Marketing Mix.